Effect of 24‐week strength training on unstable surfaces on mobility, balance, and concern about falling in older adults. (26th July 2019) - Pirauá, André Luiz Torres; Cavalcante, Bruno Remígio; de Oliveira, Valéria Mayaly Alves; Beltrão, Natália Barros; de Amorim Batista, Gabriel; Pitangui, Ana Carolina Rodarti; Behm, David; de Araújo, Rodrigo Cappato
Abstract : Objective: To evaluate the effects of 24 weeks of strength training on stable (ST) and unstable surfaces (UST) on the functional mobility, balance, and concern about falling in healthy older adults, younger than 70. Design: A single‐center randomized clinical trial. Participants: Sixty‐four older adults (58 females and 6 males; 68 years) were randomized into control, ST, or UST groups. Interventions: Both ST and UST intervention groups received a core muscle, upper, and lower limb moderate‐intensity strength exercises using stable and unstable surfaces. The classes were performed three times per week over a 24‐week period. The control group did not receive any type of active intervention. Measurements: The primary outcome measures were the dynamic balance (Berg Balance Scale (BBS)) and functional mobility (timed up and go (TUG) test). The secondary outcomes included the sitting and rising test (SRT) and Falls Efficacy Scale—International (FESI) scores. Results: There was a significant improvement in balance performance (BBS = +4 points) after 24 weeks of both ST (+1.22; 95% CI, −0.19 to 2.63) and UST (+2.26; 95% CI, 0.83‐3.70) compared with the control group. Additionally, compared with the control, only UST experienced functional mobility gains (TUG = −2.44; 95% CI, −4.41 to −0.48; SRT = +1.12; 95% CI, 0.08‐2.17) and decreased concern about falling (FESI = −4.41; 95% CI, −9.30 to −0.27). Conclusion: Long‐term ST with and without unstable devices was effective to improve dynamic balance in older adults. Furthermore, the effects of UST were extended to functional mobility gains and reduced concern about falling.